УКРАЇНСЬКА ДЕРЖАВА 1917-1920 рр.: ПРОБЛЕМА ВИРІШЕННЯ РЕЛІГІЙНОГО ПИТАННЯ (Zaporizhzhia Historical Review, 2021)
The author of the article reveals the aspects of realization of church policy of Ukrainian state during the 1917-1920. The author analyses the methods of administrative regulation of interrelations between church and state, characterizes legal base of activity of church institutions and also represents the concepts of various political forces of Ukrainian state considering the means of solving of religious problem.